From Bureaucracy to Algorithms: A Transformative Analysis of the Future of Management in the Age of Artificial Intelligence - Sakher Farea Ghalib Al-Junaid (International Journal of Education, Vocational and Social Science, 2026)
This study investigates the radical transformation in organizational systems from the traditional bureaucratic model to an "algorithmic management" model based on artificial intelligence and machine learning technologies. The study aims to analyze the structural and functional dimensions of this transformation and to foresee the future of authority and accountability in modern organizations. The study adopted a descriptive-analytical approach through a critical review of recent academic literature and studies. The findings indicate that algorithmic management redefines the concept of "administrative rationality" by automating discretionary authority, which leads to unprecedented operational efficiency but simultaneously raises ethical and legal challenges related to the "black box" phenomenon and algorithmic bias. The study concludes with the necessity of adopting a hybrid governance framework that ensures "effective human oversight" to guarantee the fairness and legitimacy of automated administrative decisions.